Can EuroSCORE II Predict the Mortality and Length of Intensive Care Unit Stay after Total Aortic Arch Replacement with Stented Elephant Trunk Implantation for DeBakey Type I Aortic Dissection? - Ge, Yipeng; Sun, Lizhong; Zhu, Junming; Liu, Yongmin; Cheng, Lijian; Chen, Lei; Zheng, Jun; Li, Chengnan; Liu, Wei (The Thoracic and Cardiovascular Surgeon, 2013)
Background EuroSCORE is a widely used objective risk scoring model.Objective The aim of this study was to evaluate the validation of EuroSCORE II for predicting in-hospital mortality and length of intensive care unit (ICU) stay after total aortic arch replacement with stented elephant trunk implantation for DeBakey Type I aortic dissection.Patients and Methods Between February 2009 and February 2012, data from 384 consecutive patients, who underwent aortic surgery using total aortic arch replacement with stented elephant trunk implantation, were collected retrospectively. EuroSCORE II was applied to predict mortality and length of ICU stay. The C-statistic was used to test discrimination of the model. Calibration was assessed with the Hosmer–Lemeshow goodness-of-fit statistic.Results The in-hospital mortality was 8.07%. The mean length of ICU stay was 3.06 days. A total of 75 patients remained at ICU for 5 days or more and 42 patients for 7 days or more. EuroSCORE II did not show good discriminatory ability in predicting mortality and length of ICU stay. The C-statistic of predicting mortality, ICU stay for 5 days or more, and ICU stay for 7 days or more were 0.49, 0.56, and 0.52, respectively. The calibration was poor for predicting mortality (p < 0.001), ICU stay for 5 days or more (p < 0.001), and ICU stay for 7 days or more (p < 0.001).Conclusion Although EuroSCORE II is the newest risk model for cardiac surgery, it is not accurate when it is applied for thoracic aortic surgery. A new risk evaluating system specially designed for aortic surgery should be developed in the future.
Keywords: EuroSCORE II; mortality; aortic dissection; intensive care unit